Reverse Shoulder Arthroplasty for Failed Proximal Humerus Osteosynthesis With Intramedullary Allograft: A Case Series - Teja Polisetty BS; Paul DeVito DO; Hyrum Judd DO; Andrew Malarkey DO; Jonathan C Levy MD (Journal of Shoulder and Elbow Arthroplasty, 2020)
Introduction The presence of retained intramedullary fibular allograft presents many challenges during reverse shoulder arthroplasty (RSA), which have been discussed in limited fashion. This case series presents a single-surgeon experience with 6 patients treated with RSA following failed osteosynthesis of proximal humerus fractures using intramedullary allografts. Methods A retrospective review was conducted of RSA patients with a minimum of 2-year follow-up (exception of 1 deceased patient) for failed plate fixation of proximal humerus fractures. Two cohorts were created based on the presence of an intramedullary allograft during the procedure. Patient-reported outcome measures, active range of motion, time to revision, surgical time, complications, and case descriptions were obtained from chart review and radiographic analysis. Results When treating patients with a retained allograft, the surgeon used a guide pin from a cannulated screw set to advance through the graft, and a cannulated drill was used to ream and bypass the allograft, contributing to a 22% increase in surgical time (151 vs 124 min). Intraoperative complications were observed only in the allograft cohort (50%; 3 of 6), including cortical perforation with cement extrusion, humeral loosening, and proximal humerus bone loss. Patients treated with a retained allograft experienced pain relief ( P   =  .001) but did not gain significant functional improvements. Conclusion RSA for failed proximal humerus fixation with healed intramedullary allograft is associated with increased operative time and intraoperative complications, and patients can mostly expect pain relief. Techniques for humeral canal preparation and stem placement to bypass the allograft are helpful in managing these revisions.